Connectivity, persistence, and loss of high abundance areas of a recovering marine fish population in the Northwest Atlantic Ocean. Issue 22 (18th October 2017) - Boudreau, Stephanie A.; Shackell, Nancy L.; Carson, Stuart; den Heyer, Cornelia E.
Abstract: In the early 1990s, the Northwest Atlantic Ocean underwent a fisheries‐driven ecosystem shift. Today, the iconic cod ( Gadus morhua ) remains at low levels, while Atlantic halibut ( Hippoglossus hippoglossus ) has been increasing since the mid‐2000s, concomitant with increasing interest from the fishing industry. Currently, our knowledge about halibut ecology is limited, and the lack of recovery in other collapsed groundfish populations has highlighted the danger of overfishing local concentrations. Here, we apply a Bayesian hierarchical spatiotemporal approach to model the spatial structure of juvenile Atlantic halibut over 36 years and three fisheries management regimes using three model parameters to characterize the resulting spatiotemporal abundance structure: persistence (similarity of spatial structure over time), connectivity (coherence of temporal pattern over space), and spatial variance (variation across the seascape). Two areas of high juvenile abundance persisted through three decades whereas two in the northeast are now diminished, despite the increased abundance and landings throughout the management units. The persistent areas overlap with full and seasonal area closures, which may act as refuges from fishing. Connectivity was estimated to be 250 km, an order of magnitude less than the distance assumed by the definition of the Canadian management units ( 2, 000 km). The underlying question of whether there are distinct populations within the southern stock unit cannot be answered with this model, but the smaller 250 km scale of coherent temporal patterns suggests more complex population structure than previously thought, which should be taken into consideration by fishery management. Abstract : A spatiotemporal analysis of juvenile Atlantic halibut in the Northwest Atlantic Ocean discovered areas of high abundance which have persisted through three different fisheries management time periods and are an order of magnitude less than current management assumptions. Identified areas are potential refuges from fishing pressure.